Novel estimation method of utility harmonic impedance based on short‐term impedance minimum variance criterion. Issue 15 (9th June 2020) - Shu, Qin; Zhao, Siliang; Xu, Fangwei
Abstract : For harmonic control of a power grid, it is prerequisite to accurately estimate and follow the utility harmonic impedance at the point of common coupling (PCC). The existing estimation methods generally consider that the utility harmonic impedance is constant, which causes the estimation error and fail in tracking of impedance fluctuations, since the utility harmonic impedance is fluctuant in practice. Actually, the harmonic impedance fluctuations will lead to the transient variation of the harmonic voltage and current which is bad for harmonic control. In this study, to follow the harmonic impedance fluctuations, a longer observation period is divided into a series of shorter period, and the fluctuations of the utility harmonic impedance over a short period are regarded as a stationary random process. Then, for each short period, the utility harmonic impedance is estimated by minimizing the fluctuation variance of the utility harmonic impedance. Besides the high estimation precision and good tracking performance of impedance fluctuations, other advantages of the proposed method are not limited by the traditional assumptions, such as the background harmonics are stable and small, the customer harmonic impedance is much larger than the utility, and the harmonic sources of both sides are independent, and so on.